A CONCEPTUAL APPROACH TO MANAGING THE PROCESS OF TRANSITION OF ORGANIZATIONS TO WORK IN THE CONDITIONS OF THE EIGHTH TECHNOLOGICAL ORDER - Glushchenko, Valery V. (International Journal of Engineering Science Technologies, 2021)
The subject of the article is the development of a concept for the transition of organizations to the eighth technological mode; the object of the article is the eighth technological mode; the purpose of the work is to increase the efficiency of the processes of transition of organizations to the eighth technological mode; to achieve this goal, the following tasks are solved: the geopolitical and socio-economic roles and results of the transition of organizations to the eighth technological mode are described; a system analysis of technological modes is carried out (tables of elements and properties of technological modes are developed); - development and description of practical tasks of the policy of transition of organizations to the eighth technological order; the structure of the policy and the content of the elements of the policy of transition to the eighth technological order are described; the criteria for evaluating the effectiveness of the policy of transition of organizations to the eighth technological order are given; the scientific methods of this article are system, historical, logical and comparative analysis, heuristic synthesis, political science, system approach, heuristic forecasting, expert methods, efficiency theory; the scientific novelty of the work is determined by the synthesis of the policy of transition of organizations to the eighth technological order, the formation of a set of criteria for assessing the geopolitical and socio-economic effectiveness of the policy of organizations for the transition to the eighth technological order